The Week - Eden, Maya (World Bank, Washington, DC, 2016)
Is a five-day workweek followed by a two-day weekend a socially optimal schedule? This paper presents a model in which labor productivity and the marginal utility of leisure evolve endogenously over the workweek. Labor productivity is shaped by two forces: restfulness, which decreases over the workweek, and memory, which improves over the workweek. The structural parameters of the model are disciplined using daily variation in electricity usage per worker. The results suggest that increases in the ratio of vacation to workdays lead to output losses. A calibration of the model suggests that a 2-3 day workweek followed by a 1 day weekend can increase welfare.